European Union and Latin America : a parternship for action - Prat I Coll, Juan (European Commission [Brussels]BE, 1994)
Traces positive developments in European Union/Latin American relations through the Rio Group, MERCOSUR, the Andean Pact aand the San Jose Process, in the fields of economics, trade and diplomacy. Examines the European Community's relations with Mexico and the Caribbean.